+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

Summer school on Adaptive Management - 2019 - CID (2019)
General description of the curriculum

edX MOOC: Adaptive Leadership in Development - edX (edX, 2016)
Gain the skills to be an adaptive leader in development and learn how to uncover local solutions to complex problems in developing countries.

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

Webinar: Operationalizing Adaptive Management: What it takes. Why it matters. - Mercy Corps (Mercy Corps, 2015)
Development actors increasingly agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. A growing body of evidence supports this claim. But what does adaptive management look like in practice? What does it require of managers and donors to make happen? How can we reconfigure incentives and success metrics to support adaptation, while remaining compliant?

Adaptive Leadership in Development course - Moran, Mark; Curth-Bibb, Jodie; Grice, Tim; Glavey, Sarah (University of Queensland, 2017)

PDIA Course: Alumni are already practicing what they learned - Samji, Salimah (Building State Capability, 2017)
written by Salimah Samji We offered 4 free PDIA online courses between November 2015 and June 2016. They were well received and 365 people, living in 56 countries, successfully completed the course…

Course: Introduction to Collaborating, Learning and Adapting (CLA) in the Program Cycle - USAID LEARN (USAID Learning Lab, 2018)